Analisis Tipologi Tingkat Urban Sprawl di Kota Padang Menggunakan Teknologi Sistem Informasi Geospasial (SIG) - Viyona Ganessa Putri; Dwi Marsiska Driptufany; Fajrin Fajrin; Defwaldi Defwaldi (Jurnal Sains dan Ilmu Terapan, 2026)
This study aims to analyze the level and typology of Urban Sprawl in Padang City in 2024 using a Geographic Information System (GIS) approach. The continuous growth of the population, along with the expansion of economic and social activities within the community, has become a major factor driving the uncontrolled expansion of urban areas toward the city’s outskirts. This phenomenon is generally characterized by increasing population density, a growing number of new buildings, changes in road network patterns, and shifts in land use from non-urban areas to built-up areas. This study utilizes several types of data, including population data, building data, new building data, the location of the city center, and road network data for the year 2024, which are analyzed spatially. The analytical method is conducted through scoring and classification techniques to identify the spatial distribution patterns of urban development and to determine three typologies of Urban Sprawl, namely low, medium, and high levels.